New interview and observation measures of the broader autism phenotype: description of strategy and reliability findings for the interview measures - Parr, Jeremy R.; Bölte, Sven (Autism research, 2015)
Clinical genetic studies confirm the broader autism phenotype (BAP) in some relatives of individuals with autism, but there are few standardized assessment measures. We developed three BAP measures (informant interview, self-report interview, and impression of interviewee observational scale) and describe the development strategy and findings from the interviews. International Molecular Genetic Study of Autism Consortium data were collected from families containing at least two individuals with autism. Comparison of the informant and self-report interviews was restricted to samples in which the interviews were undertaken by different researchers from that site (251 UK informants, 119 from the Netherlands). Researchers produced vignettes that were rated blind by others. Retest reliability was assessed in 45 participants. Agreement between live scoring and vignette ratings was very high. Retest stability for the interviews was high. Factor analysis indicated a first factor comprising social-communication items and rigidity (but not other repetitive domain items), and a second factor comprised mainly of reading and spelling impairments. Whole scale Cronbach's alphas were high for both interviews. The correlation between interviews for factor 1 was moderate (adult items 0.50; childhood items 0.43); Kappa values for between-interview agreement on individual items were mainly low. The correlations between individual items and total score were moderate. The inclusion of several factor 2 items lowered the overall Cronbach's alpha for the total set. Both interview measures showed good reliability and substantial stability over time, but the findings were better for factor 1 than factor 2. We recommend factor 1 scores be used for characterising the BAP. Autism Res 2015, 8: 522-533. © 2015 International Society for Autism Research, Wiley Periodicals, Inc.
Gesehen am 20.12.2018